A Comparative Study of Employment Competencies of Undergraduate Course of Educational Sciences in Iran and Syria - Mamdouhء Salame; Morteza Karami; Behrooz Mahram; Maghsod Amin Khandaghi (Comparative Education Society of Iran ( CESIR), 2020)
The aim of present study was to investigate competencies of employment in the field of educational sciences in Iran and Syria through comparative research method. In the qualitative section, competencies were collected through documentary study and semi-structured interviews. In this section, the participants included 8 faculty members of Department of Educational Sciences, Ferdowsi University of Mashhad and 7 members of Tartus University of Syria, which were selected by targeted sampling method. In quantitative section, expert evaluation and questionnaire were used to validate the competencies. Data analysis of qualitative part was done through open and axial coding and quantitative part was performed using mean comparison test (One Sample T-Test). The research findings showed that employability qualifications of undergraduate course in educational sciences of both universities can be divided into two groups of general and professional competencies. General competencies include four categories: intellectual, interpersonal (communication), leadership and individual skills; and specialized competencies include five categories: educational evaluation, psychological skill, technology skill, curriculum and specialized knowledge. The results of single-sample t-test showed that general competencies in both universities are same in intellectual skill, but there is a difference between two universities in individual, communication and leadership skills. The results also confirm that in terms of professional competence, both universities are similar in terms of educational and technological evaluation components, but there is a difference in psychological skills, curriculum and specialized knowledge.